Peran Datuk Ongku Mudo Sangkal dalam Islamisasi di Kampar, 1909-1927 - Rizaldi Deliskan; Abdul Karim Batubara; Jufri Naldo (Medan Resource Center, 2023)
This article delves into the history of religious leaders and founders involved in the construction of the Jami Air Tiris Mosque in Kampar Regency. Notably, Datuk Ongku Mudo Sangkal, a highly revered cleric in Tanjung Berulak village, played a pivotal role. Having received his religious education in Cdung and Taram, West Sumatra, he returned to Tanjung Berulak to propagate Islam and establish religious educational institutions for the local community. Employing qualitative research methods and a descriptive approach encompassing historical and sociological perspectives, this study utilized observation, interviews, literacy, and documentation for data collection. The research involved four sequential stages: heuristics, verification, interpretation, and historiography. Its main objective was to explore the profound contributions of Datuk Ongku Mudo Sangkal in disseminating Islam in Kampar. The findings underscore his esteemed status as a knowledgeable scholar and his significant role in fostering Islamic development in the Kampar area, particularly in Tanjung Berulak Village, Air Tiris District. The community greatly reveres Datuk Ongku Mudo Sangkal and consistently seeks his guidance to address various local issues and challenges.